Organic substitution regulated the soil microbial communities by modifying nutrient limitations in saline-alkaline soils - Yue Han; Zhanli Ma; Rui Chen; Yue Wen; Yonghui Liang; Jinzhu Zhang; Wenhao Li; Zhenhua Wang (Agricultural Water Management)
Organic amendment strategies significantly influence soil microbial community structure and functional activity, particularly in salt-affected agroecosystems. However, the mechanistic pathways by which organic substitution strategies regulate microbial resource utilization remain largely unexplored. This investigation examined the effects of organic fertilizer substitution on soil improvement and microbial community regulation in saline-alkaline soils, with a specific focus on understanding the mechanistic linkages between nutrient regulation and microbial community composition. To address this, a three-year field experiment was conducted in an arid saline ecosystem of western China. Under a constant total N input of 320 kg N ha−1, four treatments with different organic N substitution rates of urea-N were designed: CK (100 % urea-N), OF40 (organic fertilizer substituting 40 % of the urea N), OF80 (organic fertilizer substituting 80 % of the urea N), and OF100 (organic fertilizer substituting 100 % of the urea N). Following three years of differential fertilization management, the results showed that OF40, OF80 and OF100 treatments significantly enhanced soil C and N contents in the topsoil (020 cm). Compared to CK, Organic substitution treatments (OF40-OF100) enhanced soil total carbon (TC), soil organic carbon (SOC), soil total nitrogen (TN), and soil NH4+-N concentrations by 2.6180.19 %. Conversely, soil available phosphorus (AP) and NO3−-N concentrations decreased by 11.2631.16 % across OF40-OF100 treatments compared to CK. Moreover, organic fertilizer substitution significantly altered the soil bacterial community composition, enriching the populations of Firmicutes and Actinobacteriota, while also significantly increasing soil fungal alpha diversity. Mantel analysis revealed significant correlations between soil nutrient status, microbial resource limitations (indicated by enzymatic stoichiometry), and community composition. Structural equation modeling revealed that organic fertilizer substitution reduced soil salinity and AP, while increasing SOC, thereby mediating microbial C and N resource limitations that subsequently affected bacterial communities. Simultaneously, it increased SOC and decreased soil mineral N, resulting in microbial C and N resource limitations that regulated fungal communities. These findings advance our mechanistic understanding of soil amelioration processes and offer practical guidance for developing resource-efficient and environmentally sustainable fertilization strategies to improve soil quality and microbial functioning in saline-alkaline agroecosystems.